Innovations in Alzheimer’s disease diagnostic technologies: clinical prospects of novel biomarkers, multimodal integration, and non-invasive detection - Wang, Rui; Peng, Siqin; Zhu, Jianrong; Xu, Ye; Wang, Minghao; Zhang, Ling; Qiu, Yilan; Hou, Defu; Wang, Qinglin; Liu, Rushi (Frontiers in Neurology, 2025)
Alzheimer's disease (AD) is a neurodegenerative disorder characterized by the deposition of β-amyloid (Aβ) plaques and the formation of neurofibrillary tangles composed of hyperphosphorylated tau protein, ultimately leading to cognitive decline and neuronal loss. Current diagnostic methods, including clinical evaluations, neuroimaging examinations, and cerebrospinal fluid biomarker testing, face challenges such as insufficient sensitivity and specificity, as well as operational complexity. In recent years, significant advancements have been made in diagnostic technologies, with the emergence of new biomarkers and detection methods, including blood-based Aβ and tau protein detection, ocular biomarker testing, and non-invasive screening through urine or breath analysis. These innovative developments, combined with multimodal diagnostic technologies that integrate imaging, genomics, and proteomics, have opened new possibilities for the early diagnosis and precise staging of Alzheimer's disease. Furthermore, advancements in microfluidic chips and biosensor technologies have enhanced the capability for rapid, efficient, and cost-effective diagnosis. As research continues to evolve, the gradual application of these advanced technologies in clinical practice is expected to revolutionize the management of Alzheimer's disease, facilitating early intervention and the formulation of individualized treatment strategies.